Habituation, Coercion, Education: Labour in the History of Social Welfare - Gisela Hauss (Social Work and Society)
According to Judeo-Christian tradition,"In the sweat of thy face shalt thou eat bread" (Genesis 3:19). Today, this Old Testament vision seems more relevant than ever. Labour stands at the centre of public and professional discussions on integration and exclusion. Already emerging in the mid-1970s, unemployment has taken root and has resulted in what is known as base employment. Terms like"the new underclass" (Kronauer 2002, 27-71),"the useless," or the"redundant" (Castel 2008, 19) characterise current economic and social structural change. Since the 1980s, the hitherto relatively balanced working society, securely underpinned by the welfare state, has been said to be entering a period of crisis. At the same time, integration into the labour market has become immensely important in Western European societies since the 1990s. The re-individualisation of social risks (Castel 2009) has made the work imperative the prevailing dictum. Investments are aimed at human capital and at increasing employability, less at direct transfer payments. Within social welfare and social insurance schemes, this approach becomes evident in forcing beneficiaries to render services in return for benefits. Transformation towards an activating, investing, or even post-welfare state can be observed throughout Western European countries. Giuliano Bonoli has suggested that this development has also reached Switzerland, albeit in a"light" version (Giuliano Bonoli, quoted from Nadai 2010.) This article assumes that the role of social work within the new paradigm of the welfare state has hitherto been barely considered from an historical perspective. It thus aims to foster critical reflection on this issue. By reappropriating history, it seeks to open up new perspectives within the ongoing debate on activation policies in the field of social work. It focuses on three case studies concerning the significance of male and female labour in nineteenth- and twentieth-century welfare. To this end, the results of our own and other research were drawn upon (Hauss 1995, Lippuner 2005). Further, data from a recently completed research project were subject to a secondary analysis.[1] Gender was defined as a central category. The interest in these historical case studies stems from the rapidly changing debates within social work since the 1950s; these debates are surveyed in the opening paragraph of the following section. After that the cases are discussed within the context of the history of labour, the changing relationship between the welfare state and the labour market, and the accompanying shifts in gender arrangements. These shifts establish the historical context for a discussion of the case studies. The basis assumption underlying this discussion is that an historical awareness enables critical reflection on the profession's dependency on social policy and labour market developments. History raises our awareness of the thought patterns guiding institutional action in certain directions. The various points for discussion resulting from the three Swiss case studies presented here, in a country whose welfare state emerged only hesitantly, are relevant to debating social work in Europe, even if Switzerland is but one example of the many exceptions among European welfare states.